Effect of telmisartan, angiotensin‐converting enzyme inhibition, or both, on proteinuria and blood pressure in dogs - Brittany L. Fowler (Wiley, 2021)
Abstract Background The use of telmisartan (TEL), an angiotensin‐receptor blocker, for the control of systemic hypertension and proteinuria in dogs has not been reported extensively in a clinical setting. Objectives To determine the effects of an angiotensin‐converting enzyme inhibitor (ACEi) alone, ACEi in combination with TEL, or TEL alone on systolic blood pressure and proteinuria in dogs with protein losing nephropathy (PLN). Animals Forty‐two client‐owned dogs being treated for PLN. Methods Retrospective observational study of medical records of dogs at a university teaching hospital from 2012 to 2018 with the use of benazepril or enalapril alone, TEL alone, or both modalities for the management of PLN. Noninvasive blood pressure and urine protein to creatinine ratio (UPC) were compared among the treatment groups over time. A multivariable mixed‐effects linear regression model followed by post hoc analysis was used to estimate the marginal means and differences between the treatment groups. Results In comparison to group ACEi alone, combination treatment of an ACEi with TEL significantly reduced (P = .007) systolic blood pressure by 13 mm Hg (95% confidence interval [95% CI]: 4‐22 mm Hg). Angiotensin‐converting enzyme inhibitor + TEL in comparison to ACEi alone showed significant (P = .01) reduction in UPC of 2.5 (95% CI: 0.6‐4.4). The UPC of group ACEi + TEL was significantly lower (P = .01) in comparison to TEL alone by 3.8 (95% CI: 0.8‐6.8). Conclusions and Clinical Importance Telmisartan can be used to treat systemic hypertension and proteinuria in dogs.